MODELING METHOD OF DYNAMIC CHARACTERISTICS OF BOLTED CONNECTION BASED ON CONTACT BOUNDARY AND FRACTAL THEORY - LU ShiKun; HUA DengXin; LI Yan; LI PengYang; CUI FangYuan (Jixie qiangdu)
Aiming at the problem of dynamic characteristic modeling of bolted connection structure considering the influence of roughness,a new model of bolted connection with rough surface joint surface replaced by spring damping model is established,which considers the influence of various factors such as bolt,gasket and rough joint surface on vibration characteristics. The model is based on the fractal theory of mechanical surface,and the calculation formula of the joint stiffness is obtained. Based on the finite element contact results,the spring layout of the spring damping model is determined,and the influence of the number of spring layouts on the vibration characteristics is studied. The experimental results show that the results of this method are very close to the experimental results,which show that this method is effective.